2017
DOI: 10.21037/jovs.2017.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Technological aids in uniportal video-assisted thoracoscopic surgery

Abstract: With the evolution of uniportal video-assisted thoracoscopic surgery (VATS), the technological aids have come to help skill surgeons to improve the results in thoracic surgery and feasible to perform a complex surgery. The technological aids are divided into three important groups, which make surgical steps easy to perform, besides reducing surgical time and surgical accidents in the hands of experienced surgeons. The groups are: (I) conventional thoracoscopic instruments; (II) sealing devices using in uniport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Recently, with the development of the concept of rapid rehabilitation surgery, there is a gradual increase in the use of UVATS that requires only one incision. 18 Studies have shown that this surgical method has more advantages in reducing surgical trauma and postoperative pain. 2 , 18 - 21 Kapicibasi et al 2 have shown that using UVATS not only allows to safely perform lung biopsy and resection, but is also safe for bullectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, with the development of the concept of rapid rehabilitation surgery, there is a gradual increase in the use of UVATS that requires only one incision. 18 Studies have shown that this surgical method has more advantages in reducing surgical trauma and postoperative pain. 2 , 18 - 21 Kapicibasi et al 2 have shown that using UVATS not only allows to safely perform lung biopsy and resection, but is also safe for bullectomy.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Studies have shown that this surgical method has more advantages in reducing surgical trauma and postoperative pain. 2 , 18 - 21 Kapicibasi et al 2 have shown that using UVATS not only allows to safely perform lung biopsy and resection, but is also safe for bullectomy. Zhang J et al 20 also reported that patients who undergo UVATS have less trauma, which is beneficial for lung function and postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%